Relationship of Socioeconomic Status with Special Reference to Leucorrhoea: Socioeconomic Status with Leucorrhoea - Altaf, Nagina; Yousaf Quddoos, Muhammad; Mahmood, Shahid; Anees Ur Rehman, Muhammad; Sami Ullah, Tayyaba; Ainee, Ammara; Fatima, Areeja; Kauser, Samina; Yaqub, Shazia; Hussain, Ashiq (Pakistan Journal of Health Sciences, 2022)
Leucorrhoea is a common female problem; recurrent especially in women of reproductive age that may or not be associated with vaginal infection or elevated estrogen levels. It may accompany vaginal discharge, vulvae burning and itching, low backache, pains in lower abdomen and legs, general weakness and loss of appetite. This disorder is associated with psychological, physiological and pathological problems. Objectives: To investigate nutritional status of girls having leucorrhoea. The aim of this study was nutritional health status assessment of girls of university with special reference to leucorrhoea. Methods: The volunteer girls of sample size 150 were interviewed in the study. For this study leucorrhoea is categorized into 3 group’s mild moderate and severe. Results: The volunteers were from university of Sargodha between the ages of 16-40. In this study it was observed that out of 150 volunteers 82.5% were leucorrheal and 17.33% were none leucorrheal physiological status of girls were mostly influenced by socioeconomic status like 53.33% girls belong to lower middle income group and physical activity was also a major factor for leucorrhoea like most girls with leucorrhoea have sedentary lifestyle (56.66%). Further it was notice that one of the major causes of severe leucorrhoea was constipation which affects 76.47% girls. Conclusions: Leucorrhoea can be reduce or by better our socioeconomic status eating well natural food, reduce tension of income and overcome constipation which is bone of contention. If we stay in nature the diseases will avoid us.